Manajemen Komunitas Belajar dalam Implementasi Pembelajaran Mendalam di SDN Bojongpicung 2 Kabupaten Cianjur - Dadang Suhardiman; Indra Eka Permana; Sri Mulyani; Wildan Abdillah; Dinny Mardiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This research aims to describe the management of learning communities in implementing deep learning at SDN Bojongpicung 2, Cianjur Regency. This qualitative descriptive research involved 10 teachers, 1 principal, and 76 fourth-grade students as research subjects. Data collection techniques used observation, interviews, and documentation. Data analysis used the Miles and Huberman model including data reduction, data display, and conclusion drawing. The results showed that learning community management at SDN Bojongpicung 2 includes four stages: planning, organizing, implementation, and evaluation. Planning involves setting goals and forming community structures. Organizing includes role division and task coordination. Implementation is carried out through collaborative learning, peer tutoring, and reflective discussions using inquiry cycles consisting of initial reflection, planning, implementation, and evaluation. Evaluation is conducted periodically to measure community effectiveness. Deep learning implementation through learning communities shows significant improvements in students' critical thinking, collaboration, and problem-solving skills with an average N-Gain of 0.65 in the medium category. The success of the learning community is supported by exemplary leadership, collaboration culture, and a healthy work environment.